Історико-культурна спадщина української діаспори в сучасній туристичній практиці - Кузіна, Наталія Вікторівна; Іваницька, Л. (Київський національний університет імені Тараса Шевченка, 2022)
Досліджується історико-культурна спадщина української діаспори та її роль у сучасній туристичній практиці. Засновуючись на аналізі документальних джерел, архівних матеріалів та наукових студій, розглядається вплив української діаспори на розвиток туризму, зокрема через збереження та презентацію культурних, історичних та архітектурних пам'яток. Висвітлюються основні напрями туристичної активності української діаспори, включаючи організацію культурних заходів.

The article explores the historical and cultural heritage of the Ukrainian diaspora and its significance in contemporary tourism practices. It analyzes the various aspects of the diaspora's heritage, including the organization of cultural events, preservation of traditions and customs, and the role of Ukrainian communities abroad in promoting Ukrainian culture. The article also examines the impact of the diaspora's heritage on tourism, highlighting its potential for attracting tourists interested in exploring Ukrainian history and culture. Overall, the article emphasizes the importance of the Ukrainian diaspora's heritage in enhancing tourism experiences and fostering cultural exchange.
Historical and Cultural Heritage of the Ukrainian Diaspora in Modern Tourism Practice
Keywords: діаспора; українська діаспора; історико-культурна спадщина української діаспори; громадське життя; національна ідентичність; diaspora; Ukrainian diaspora; historical and cultural heritage of the Ukrainian diaspora; public life; national identity